Increasing flooding tolerance in rice: combining tolerance of submergence and of stagnant flooding - Kato, Yoichiro; Collard, Bertrand C. Y.; Septiningsih, Endang M.; Ismail, Abdelbagi M. (Oxford University Press, 2019)
Rice ecosystems in the tropical coastal areas are subject to two types of flooding stress: transient complete submergence and long-term water stagnation (stagnant flooding). Here, we aimed to dissect the mechanisms for stagnant flooding tolerance of rice genotypes carrying SUB1, a quantitative trait locus for submergence tolerance.We screened 80 elite genotypes under stagnant flooding stress in the lowland rice fields in the wet and dry seasons, and examined the tolerance mechanisms of promising genotypes for the two following seasons.Yield reduction under stagnant flooding averaged 48 % in the dry season and 89 % in the wet season. Elite genotypes carrying SUB1 showed 49 % lower yield than those without SUB1 under stagnant flooding, with no differences under shallow water conditions. However, we identified a few high-yielding Sub1 genotypes that were as tolerant of stagnant flooding as a reference genotype that lacked SUB1. These genotypes had intermediate stature with more shoot elongation in response to rising water than a moderately tolerant Sub1 reference variety, resulting in greater canopy expansion and higher yield. It was important to increase lodging resistance, since plant height >140 cm increased lodging under stagnant flooding. The culm diameter was closely associated with culm strength; reduced aerenchyma formation and increased lignin accumulation in the culm should increase lodging resistance.The study demonstrated a successful combination of submergence and stagnant flooding tolerance in a rice breeding programme, and identified elite Sub1 genotypes that also tolerate stagnant flooding. Our results will support genetic improvement of Sub1 varieties for stagnant flooding tolerance.